Subjective Well-Being of 10- and 12-year-old Children in the Space of Satisfaction with Family, School and Friends - Bruk Zh.Yu; Ignatjeva S.V (Moscow State University of Psychology and Education, 2022)
The research presented in the article aims to identify the joint influence of family, school relationships and relationships with friends on overall life satisfaction and subjective well-being in children. The experiment was implemented within the framework of the International Survey of Children's Well-being - Children's Worlds (ISCWeB).In the course of the study we have developed a special set of tools for classifying children's satisfaction with family, school, and friends. The analysis of the formed clusters allowed us to take into account the multidimensionality and heterogeneity of the phenomenon. The adaptation and testing of the proposed technique was carried out on a sample of 1959 schoolchildren of the Tyumen region, aged 10 and 12 years. According to the results, the number of clusters formed and their qualitative composition are not uniform, which confirms the age dynamics of the phenomenon.10-year-old children are more categorical in assessing their well-being and satisfaction with life: they are either satisfied with life or not satisfied.12-year-old children are more detailed in assessing life satisfaction; they are able to identify various spheres and aspects of their lives and to carry out a differentiated assessment.